History and evolution of a journal club specialized in veterinary pharmacology: an opportunity to learn and grow in a virtual and stimulating community - Abdul Kadir, A.; Vercelli, C.; Sitov, A.; Henklewska, M.; Giorgi, M. (John Wiley & Sons, 2023)
The requirement to be constantly updated about the most important scientific innovations in veterinary pharmacology is normally perceived by those involved in research. In response to this need, a small group of veterinary pharmacologists funded a Journal Club (JC) in 2012. This JC was designed to give the opportunity of regularly discussing current and emerging topics in veterinary pharmacology. At first, JCs were “live” session and then they became virtual weekly meeting held via Skype. Additional members have been enrolled along the following 10 years reaching a global distribution. In 2020, a paper has been published to report our experience (1). Currently the group consists of 30 participants.